UJI AKTIVITAS ANTIDIABETES, ANTIHIPERLIPIDEMIA, DAN ANTIATEROSKLEROSIS KOMBINASI EKSTRAK TERPURIFIKASI HERBA SAMBILOTO (Andrographis paniculata(Burm.f.)Ness.) DAN METFORMIN PADA TIKUS DIABETES MELLITUS TIPE 2 RESISTEN INSULIN - , EKA SISWANTO SYAMSUL, Dr. Agung Endro Nugroho, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Diabetes Mellitus (DM) type 2 is a disorder that has characteristic hyperglycemic conditions, impaired metabolism of carbohydrates, fats and proteins are characterized by insulin resistance and or insulin deficiency. Insulin resistance is characterized by an increase in lipolysis and hepatic glucose production and reduction of intake of glucose into muscle or adipose cells. Sambiloto (Andrographis paniculata (Burm.f.) Ness.) is a plant that can be used to overcome the disease diabetes. In DM therapy there is a possibility of the use of therapy with oral hypoglycemic agents, such as metformin. This study aims to determine the potential of the combination of purified extract of sambiloto herbs and enhancement effects of metformin on blood glucose levels decrease, antihiperlipidemia, and antiaterosklerosis in insulin resistant rats. The research was conducted using a complete random method indirectional pattern. Test animals used were divided 4 groups, group 1: metformin 45 mg / kg (positive control), group 2: purified extract of sambiloto herbs 434.6 mg/ kg, group 3: a combination of metformin 45 mg / kg BW with the extract of 434.6 mg/ kg (combination 1), and group 4: metformin 22.5 mg/ kg body weight with extract 434.6 mg/ kg (combination 2). Test animals are insulin resistant type 2 DM was made by administering 1.8 g fructose / kg body weight and fat diet for 50 days. Assay of glucose, triglycerides, LDL and cholesterol using a reagent kit. Observation of GLUT-4 expression in muscle cells by using immunohistochemical techniques. Observation of atherosclerosis in the aorta preparations rats using histopathologic techniques with haematoxylin-eosin staining. Insulin resistance rats was tested by using three parameters: (1) testing of blood glucose levels preprandial and postprandial (2) the hypoglycaemic activity of glibenclamide, and (3) observations of GLUT-4 protein expression in muscle tissue. Test results show that the test animals had insulin resistant. Results, in this research antidiabetic and antihyperlipidemic activity assay indicate that the hypoglycaemic, the reduction LDL and triglycerides in blood for combination 1 and combination 2 lower compared to a single administration of metformin (p<0,05). Test results showed that treatment of metformin, purified extract or a combination of both can not lower blood cholesterol levels significantly. Observations atherosclerosis indicates that treatment of metformin, purified extract or a combination of both did not have the power antiaterocklerosis after being administered for 5 days. From the above results concluded that the combination of sambiloto extract purified with metformin does not increase the potency of antidiabetic and antihyperlipidemic in single use.